Pengaruh Pengawasan Pimpinan Terhadap Kinerja Pegawai Dalam Mendistribusikan Bahan Bakar Minyak pada Satuan Perbekalan Detasemen Markas (Studi di Markas Besar Tentara Nasional Indonesia) - Ngajito Ngajito (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2022)
This study aims to determine the influence of leadership supervision on the performance of employees in distributing fuel oil in the Unit of the Indonesian National Army Headquarters Detachment Supplies. How big is the influence of leadership supervision on the performance of employees in distributing fuel oil at the Indonesian Armed Forces Headquarters Supplies Detachment Unit. The method used is descriptive research method with a quantitative approach. Sampling in this study uses a saturated census or sampling technique, namely the method of sampling research if all members of the population are used as samples. So, the sample in this study amounted to 25 respondents. Based on the results of the study, it can be concluded as follows: the supervision of the leadership belongs to the excellent category. Furthermore, from the results of the average score obtained that the employee's performance has utilized the working time optimally to produce the expected output by the organization with an average score of 84.98% indicating that the performance of employees in distributing fuel is included in the excellent category. The results show that leadership supervision has an influence on the performance of employees in distributing fuel oil in the TNI Headquarters Detachment Supplies Unit of 53.2%.